Consensus on the terminologies and methodologies for masticatory assessment - Gonçalves, Thais Marques Simek Vega; Schimmel, Martin; van der Bilt, Andries; Chen, Jianshe; van der Glas, Hilbert W.; Kohyama, Kaoru; Hennequin, Martine; Peyron, Marie‐Agnès; Woda, Alain; Leles, Claudio Rodrigues; Pereira, Luciano (Journal of oral rehabilitation, 2021)
A large number of methodological procedures and experimental conditions are reported to describe the masticatory process. However, similar terms are sometimes employed to describe different methodologies. Standardisation of terms is essential to allow comparisons among different studies. This article was aimed to provide a consensus concerning the terms, definitions and technical methods generally reported when evaluating masticatory function objectively and subjectively. The consensus is based on the results from discussions and consultations among world‐leading researchers in the related research areas. Advantages, limitations and relevance of each method are also discussed. The present consensus provides a revised framework of standardised terms to improve the consistent use of masticatory terminology and facilitate further investigations on masticatory function analysis. In addition, this article also outlines various methods used to evaluate the masticatory process and their advantages and disadvantages in order to help researchers to design their experiments.